Research Progress on Comprehensive Traditional Chinese Medicine Therapy for Lumbar Disc Herniation in the Past Decade - Zhang, Yunqing; Cai, Xuefeng; Shen, Xiaofeng (Journal of Contemporary Medical Practice, 2025)
In recent years, with the acceleration of the pace of life, poor lifestyle habits have led to a gradual increase in the incidence of lumbar disc herniation (LDH), with a trend towards younger age groups, resulting in a significant social burden. However, conservative treatments face challenges such as considerable individual variability in efficacy and the need for repeated medical visits, which can lead to poor patient compliance. Traditional Chinese medicine (TCM) offers a variety of external therapies for LDH, including acupuncture, tuina (therapeutic massage), herbal plasters, fumigation, moxibustion, and their combinations. These therapies collectively contribute to reducing inflammatory factor levels, alleviating tissue adhesions, improving lumbar function, decreasing lumbar fibrosis, enhancing neuroelectrophysiological function, and lowering recurrence rates. In clinical practice, multiple TCM therapies are often combined to address both the symptoms and root causes of the disease. Through literature review, this paper summarizes the research progress on comprehensive TCM therapies for LDH over the past decade, aiming to provide references for current TCM treatment methods and research mechanisms related to LDH.